A density functional study on structural, electronic, chemical and optical properties of Ag-X, Al-X and Cu-X [X=Li, Na, K] nano-alloys for OPTO-electronic and catalytic applications / Shaikat Debnath - Shaikat, Debnath (2015)
Over the past few decades, the progress in nanotechnology has impacted every aspect of science and technology. Among all the physical and chemical properties of the nanomaterials, the optical characteristics are of special interest because of their plasmonic phenomenon. Among the conventional plasmonic materials, Ag and Au are the mostly used. However, their high interband transition losses in optical frequencies and high price are restricting them from extensive commercial usage. Apart from Ag and Au, Cu and Al can come as low cost alternatives, which exhibit interesting plasmonic behavior. But unfortunately, none of them display optical properties as good as silver and gold. In contrast, it is reported that Li, Na and K possess the best plasmonic quality among all metals reported to date. But due to their very high reactivity towards air and water, it is very challenging to use their nanoparticles solely. Thus, in this work we have proposed Ag-X, Al-X and Cu-X [X=Li, Na, K] nanoalloys, whereas Ag-X is a potential improvement over Ag and Al-X and Cu-X nanoalloys can be considered as the low cost alternative of silver and gold. To evaluate the structural and electronic stability, chemical and optical properties of the upper-mentioned nanoalloys, a 13-atoms core-shell structure is selected as the quantum model, while Accelrys Materials studio is used for the density functional (DFT) calculations. In the framework of DFT, the geometrical stability of all the nanoalloys is checked through vibrational analysis and bond length comparison, which is followed by binding energy and HOMO-LUMO gap calculations to ensure the electronic stability. Later ionization potential and electronic affinity of the nanoalloys were calculated to predict their chemical nature. Finally, time dependent density functional calculations are carried out to observe the optical absorption spectra of the clusters, which was followed by partial density of states calculations. From the calculations, it is evident that all of the Li and Na doped clusters have exhibited higher chemical stability, whereas their anions are found very reactive. Thus, all of the aforesaid Li and Na doped clusters can be excellent potential for catalytic applications. In addition, doping has yielded significant changes in the optical absorption spectra of the nanoalloys. For the Ag-X and Cu-X nanoalloys, noticeable improvement was observed in absorption intensity in visible and UV-Vis optical ranges as a result of doping. Typically, solar cells absorb light in the visible and UV-Vis regions, hence these Ag-X and Cu-X clusters can bring attention-grabbing heightening as a replacement of silver and gold nanoparticles in the thin film solar cells, as well as other opto-electronic applications. On the contrary, Al-X clusters are found to exhibit remarkable wide optical absorption band gap in UV optical spectra, for why it will be an excellent potential for UV-absorption applications such as UV-therapy, UV-coating etc. Thus it can be concluded that all of the Ag-X, Al-X and Cu-X [X=Li, Na, K] nanoalloys have outstanding electronic and optical properties and can be excellent potential for the applications in opto-electronics and catalysis.